Die Deutschen: Profil einer Nation - Weidenfeld, Werner (Klett-Cotta, 1991)
Werner Weidenfeld, Karl-Rudolf Korte: Die Deutschen. Profil einer Nation. Klett-Cotta Verlag, Stuttgart 1991. 275 Seiten, 68,- DM